Treating marital violence within intact couple relationships: outcomes of multi-couple versus individual couple therapy - Stith, Sandra M.; McCollum, Eric E.; Rosen, Karen H.; Thomsen, Cynthia J. (My University, 2013)
An experimental design was used to determine outcomes of a domestic violence-focused treatment program for couples that choose to stay together after mild-to-moderate violence has occurred. Forty-four couples were randomly assigned to either individual couple or multi-couple group treatment. Nine couples served as the comparison group. Male violence recidivism rates six-months after treatment were significantly lower for the multi-couple group (25%) than for the comparison group (66%). In contrast, men in the individual couple condition were not significantly less likely to recidivate (43%) than those in the comparison group. Likewise, marital satisfaction increased significantly, and both marital aggression and acceptance of wife battering decreased significantly among individuals who participated in multi-couple group therapy, but not among those who participated in individual couple therapy or the comparison group.
Treating intimate partner violence within intact couple relationships: Outcomes of multi-couple versus individual couple therapy.
Keywords: Domestic violence; Couples treatment for domestic violence; Multi-couple treatment for domestic violence; Intimate partner violence